-2(3x-4)-x-3=33

1 answer

To solve the equation -2(3x-4)-x-3=33, we can start by simplifying the left side of the equation:

-2(3x-4) can be rewritten as -6x + 8.

Substituting this back into the equation, we have:

-6x + 8 - x - 3 = 33

Combining like terms, we get:

-7x + 5 = 33

Next, we can isolate the variable term by subtracting 5 from both sides of the equation:

-7x = 33 - 5

Simplifying, we have:

-7x = 28

To solve for x, we divide both sides of the equation by -7:

x = 28 / -7

Simplifying further, we get:

x = -4

Therefore, the solution to the equation -2(3x-4)-x-3=33 is x = -4.